KEBONDOWO VILLAGE COMMUNITY DEVELOPMENT DISTRICT DISTRICT Banyubiru Semarang through VILLAGE TOUR PROGRAM - arum puspita nugraheni; kushandajani kushandajani; puji astuti (Journal of Politic and Government Studies, 2015)
Community empowerent is a solution to alleviate poverty problems in Indonesia. By looking at the potential of rural tourism is very abundant, the government issued a community empowerment program through the tourist village. Kebondowo Tourism Village is one of the first of 14 tourist villages in the district of Semarang. However, since early 2009 the village was used as a tourist village did not show significant impact on the reduction of the number of poor families and the welfare of Kebondowo village. Thus this study aims to determine the factors that hinder the development of this tourist village program and to provide suggestions for the village and Pokdarwis Tourism Village Kebondowo to face many obstacles that exist so that this tourist village program can run smoothly and improve the welfare of citizens. The purpose of this study was to identify factors for the failure of community empowerment through Village Tourism Kebondowo program and to provide input in overcoming the obstacles that hinder the development of tourism village Kebondowo. This study is a qualitative research method, the type of research used in this research is descriptive analytic study. Data taken from the interview has yet, documentation, and data from documents of the village. By looking at the studies in the field and interviews, the factors that inhibit include the human resource due to the low level of education of rural communities and its minimal training to improve human resources rural communities. The second thing is a non-human resource factor (SDNM), among others, the lack of facilities in tourist areas, a lack of funding to the passage of a tourist village program, the shortage of accommodation and infrastructure is not good. The last factor is communication, poor communication between government and Pokdarwis Tourism Village Kebondowo with the Municipality of Semarang and Central Java Provincial Government. Therefore it is very necessary concrete efforts from the government and village communities to jointly develop tourism villages by improving rural infrastructure, building adequate facilities, makes the work of the villagers into a tourist attraction, giving special attention to providing special funding for tourist villages and improve communication patterns between rural and government. Some of the factors that hinder the development of village tourism is a human resources, village facilities, rural infrastructure, communication is woven villages and lack of funding. Some of the solutions offered are training to villagers Kebondowo human resources, giving special budget for tourism activities, Improving your rural infrastructure and increase community participation.